The thermophysical and microstructural effects of an artificial ice layer in natural snow under kinetic growth metamorphism - Greene, Ethan M., author; Smith, Freeman, advisor; Elder, Kevin, advisor (Colorado State University. Libraries, 2007)
The macrostructure of a seasonal snow cover evolves with each new weather event. With wind and precipitation, layers of snow coat the old snow surface and the microstructure within these layers develops as a function of the environmental conditions. The thermal, mechanical and optical properties of snow are highly dependent on its microstructure. Many researchers have investigated metamorphism in homogenous snow, but little is known of snow metamorphism at the interface of two layers. In this study I observe the thermal and microstructural evolution of layered and non-layered samples of natural snow in kinetic growth metamorphism. The layered samples contain a 4 mm thick ice layer, which creates a large gradient in thermal conductivity and porosity. I collected samples of natural snow with a density range of 150-290 kg m-3 from the mountains of northern Colorado. In a cold laboratory, I subjected paired, treatment (layered) and control (non-layered), samples to a vertical temperature gradient of 60-110 K m-1 for a period of 5 days. During the experiment I measured the heat flux at the boundaries and the temperature profile within the sample. At the end of each experiment I cast the snow samples and performed serial sectioning and three-dimensional reconstruction of the snow microstructure. I also used the thermophysical data and microstructural data to simulate the evolution of the microstructure and the thermal state at the end of the experiment. The temperature profiles show snow in a steady-state thermal environment. There is no consistent signal from the ice layer in the temperature data. The microstructure within the snow samples undergoes a dramatic change during the experiments. In the control samples vertical chains of faceted and hollow particles develop and are responsible for transporting most of the thermal energy in the sample. Faceted structures grow off the bottom of the ice layer, while the upper surface erodes and becomes smooth and round. The presence of the ice layer affects thermal, mechanical and optical properties of the snow, these effects occur within several particles of the interface and would be difficult to detect with standard field techniques.
Keywords: artificial ice; ice; kinetic growth; snow; thermophysical; geophysics; atmosphere; atmospheric sciences